2022
DOI: 10.1101/2022.08.11.503686
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effects of Cr stress on bacterial community structure and diversity in rhizosphere soils of Iris pseudacorus

Abstract: Rhizosphere microorganisms play an important role in improving soil microenvironment, which contributes to plant growth under heavy metal stress. However, the effect of chromium (Cr) on plant rhizosphere bacterial community is still unknown. In this paper, sole-cultivated pattern, two-cultivated pattern and three-cultivated pattern, combined with 16S rRNA high-throughput sequencing technology, the effects of Cr stress on bacterial community structure and diversity in rhizosphere soil of Iris Pseudacorus were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…Previous studies have found that the increase in the abundance of Acidobacteriota can promote the absorption of Cd by plants because organic acids secreted by Acidobacterium can promote the release of Cd from soil colloids (Ganesh et al, 2022). In this study, with the passage of Cr stress time, the abundance of Acidobacteriota decreased to 3.82% in Group Cr21 (Figure 4E), which may be caused by the decrease of Cr content in the rhizosphere with the extension of Cr stress time (Wei et al, 2023c). Rhizosphere microorganisms can induce the production of flavonoid antioxidant substances in plants, thereby enhancing the resilience of plants to oxidative stress (Wang et al, 2022b).…”
Section: Discussion Mechanism Of Rhizosphere Bacteria and C Indica ...mentioning
confidence: 45%
See 1 more Smart Citation
“…Previous studies have found that the increase in the abundance of Acidobacteriota can promote the absorption of Cd by plants because organic acids secreted by Acidobacterium can promote the release of Cd from soil colloids (Ganesh et al, 2022). In this study, with the passage of Cr stress time, the abundance of Acidobacteriota decreased to 3.82% in Group Cr21 (Figure 4E), which may be caused by the decrease of Cr content in the rhizosphere with the extension of Cr stress time (Wei et al, 2023c). Rhizosphere microorganisms can induce the production of flavonoid antioxidant substances in plants, thereby enhancing the resilience of plants to oxidative stress (Wang et al, 2022b).…”
Section: Discussion Mechanism Of Rhizosphere Bacteria and C Indica ...mentioning
confidence: 45%
“…In addition, during the seedling culture period, Hoagland solution (15 ml) and water (15 ml) were added into the soil culture pot every 15 and 3 days successively. If Cr was added to the stress experiment, the Hoagland nutrient solution was not required (Si et al, 2022;Wei et al, 2023c).…”
Section: Plant Culturesmentioning
confidence: 99%
“…Longterm nitrogen deposition may also decrease the available organic matter of soil microorganisms, reducing microbial activity and diversity. Another study found that the presence of certain pollutants, such as chromium, can also reduce alpha diversity (Wei et al, 2023). Although we do not have data regarding nutrient and contaminant concentrations, bodies of water near farms often have high concentrations of these nutrients and heavy metals due to agricultural practices.…”
Section: Diversity Indexesmentioning
confidence: 83%